Semmelweis Caring University Model Program Based on the Development of a Center of Preventive Services: Health for All Employees at a University Occupational Setting - Ungvári, Zoltán; Ádány, Róza; Szabó, Attila J.; Dörnyei, Gabriella; Moizs, Mariann; Purebl, György; Kalabay, László; Varga, Péter; Torzsa, Péter; Kellermayer, Miklós; Merkely, Béla (Frontiers in Public Health, 2021)
The leadership of the Semmelweis University as a leading institution of higher education in Hungary and the Central Eastern European region within the area of medicine and health sciences has decided to reflect the unfavorable public health situation in the country as well as the deteriorating health behavior and health status indicators in the Hungarian population by the development of an occupational setting-based personalized public health model program targeting its about 8500 employees. Based on its infrastructure and human resources the core element of the program is the establishment of the Center of Preventive Services (CPS) with units providing health risk assessment for each employee, and whenever necessary consultation with medical specialist in preventive medicine and public health, as well as counselling with dietician, physiotherapist and/or health psychologist. The service providers are the staff members of the relevant faculties in collaboration with partner primary and occupational care physicians. The units of the CPS can also serve as practical training sites for students at various levels of medical and health sciences training, and strongly contribute to the development and improvement of their skills to be able for working as a team in service provision. The employees are not only beneficiaries of health risk assessment and screening repeated on a regular basis and adequate interventions at the right time, but they also serve as a sample for a longitudinal cohort study and further ad hoc surveys for defining and implementing interventions to support health protection, disease prevention and healthy aging among them.